2020
DOI: 10.7759/cureus.6984
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Histoplasma duboisii Brain Abscess and Review of the Literature

Abstract: Histoplasmosis is a fungal disease caused by Histoplasma capsulatum var. capsulatum (Hcc) and H. capsulatum var. duboisii (Hcd). Central nervous system (CNS) involvement is rare. So far, the few cases reported having Histoplasmosis associated brain abscesses were caused by H. capsulatum var. capsulatum. Herein, we report a unique case of brain abscess caused by H. capsulatum var. duboisii occurring in a 42-year-old immunocompromised woman with HIV. Initially, she presented with hypothermia, vomiting, frontal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…We found 1159 studies and included 108 manuscripts published between 1962 and 2022, totaling 298 patients 7–10,12–115 . We excluded 38 articles that could not be retrieved.…”
Section: Resultsmentioning
confidence: 99%
“…We found 1159 studies and included 108 manuscripts published between 1962 and 2022, totaling 298 patients 7–10,12–115 . We excluded 38 articles that could not be retrieved.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the dominance of cutaneous, subcutaneous, and osseous manifestations of histoplasmosis among Africans highlights some uncertainty. However, it has been widely suggested that Hcc and Hcd share similar infection route with the inhalation phenomenon, but may disseminate to the skin, lymph nodes, or bones by hematogenous or lymphatic spread [ 8 10 ]. The transcutaneous route after trauma has also been suggested especially in Hcd and has been implicated in a few case reports on detection of lesion development at sites of acupuncture needle pricks after mud bath [ 26 ] and tribal scarification or tattoos [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lymphadenopathy usually accompanies skin lesions; it is mostly superficial, confined to the area of lymph drainage, or generalized in disseminated disease. In very rare cases, internal organs may be affected, mimicking cancers [ 8 10 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another fungal CNS infection that has been emerging in Africa is histoplasmosis, caused by the dimorphic fungus Histoplasma capsulatum with the var. duboisii being characteristically prevalent in Africa (39,40). This fungus is the most common pathogenic dimorphic fungus causing endemic infections in Central and West Africa and in the island of Madagascar (41).…”
Section: Epidemiology Of Cns Fungal Infections In Africamentioning
confidence: 99%